Implementing knowledge sharing in construction industry firms [electronic resource] - Winnie, Bong Chui Nyuk, 1987- (2011)
Thesis (Sarjana Sains (Pengurusan Pembinaan)) - Universiti Teknologi Malaysia, 2011